Festival Muharram sebagai Sarana Pengembangan Minat dan Bakat Anak: Studi Kasus di Desa Kadilangu - Dwi Henggar Saputra; Qonita Nurun Ni’ma Amalia; Ika Asmani Nanda Setya Husada (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to increase children's interests and talents through various competition activities held at the Muharram Festival in Kadilangu Village. It is hoped that this activity can provide space for children to develop their potential and strengthen social interactions in the community. The method used in this research is descriptive qualitative, with direct observation during the activity and in-depth interviews with the event committee, competition participants and parents. The main data source comes from the participation of kindergarten to elementary school children who take part in competitions such as coloring, drawing, memorizing letters, and calling to prayer. The research results show that competition activities at the Muharram Festival are able to increase children's interest in participating in creative and competitive activities, as well as building their self-confidence. Apart from that, this activity succeeded in revealing children's hidden talents in the fields of art and religious knowledge, which were previously less facilitated in formal environments. Based on these results, it is proposed that similar activities can continue to be carried out periodically to support the development of children's interests and talents in the village